2020
DOI: 10.9734/jpri/2020/v32i1030495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foeniculum vulgare Fortified Diet on Coagulation Profile and Some Biochemical Parameters

Abstract: Aims: Coagulation profile shows the clotting ability of blood. Biochemical tests indicate health status of vital organs such as liver, heart and kidneys. Herbal products are being assessed for their role in affecting these parameters. We evaluated role of Foeniculum vulgare incorporated diet on coagulation profile and some important biochemical parameters. Study Design:  Laboratory centred randomized controlled trial. Place and Duration of Study: Pharmacology Department of University of Karachi, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Hormones are an essential part of the system that regulates the major functions of the body. Testosterone and the luteinizing hormones are the important hormones of the male reproductive system (Abbas et al, 2020). In the present study, there was a significant (p<0.001) decrease in the testosterone levels, while a significant increase (p<0.001) in the luteinizing hormone was observed in the arsenic-treated groups in comparison to the control group of rats.…”
Section: Discussionsupporting
confidence: 47%
“…Hormones are an essential part of the system that regulates the major functions of the body. Testosterone and the luteinizing hormones are the important hormones of the male reproductive system (Abbas et al, 2020). In the present study, there was a significant (p<0.001) decrease in the testosterone levels, while a significant increase (p<0.001) in the luteinizing hormone was observed in the arsenic-treated groups in comparison to the control group of rats.…”
Section: Discussionsupporting
confidence: 47%
“…Similarly, an earlier study showed that linolenic acid, a constituent of F. vulgare, increases the amount of neurotransmitters in the brain (Acar et al, 2002). The antidepressant action of Foeniculum vulgare seeds has been shown in a study by Abbas et al (2020), on albino smiley moths with different concentrations (2% and 4%). These results suggest that fennel oil alone may be potential alternatives to antidepressant drugs to treat depression.…”
Section: Neurobehavioral Tests Forced Swimming Testmentioning
confidence: 67%
“…The traditional use of this plant has proven its beneficial effect as an antidepressant (Abbas et al, 2019;Abbas et al, 2020). Similarly, the aromatic essential oil of Foeniculum vulgare has been successfully used for the management of depression (Glory et al, 2015).…”
Section: Neurobehavioral Tests Forced Swimming Testmentioning
confidence: 99%
“…Abbas et al studied how serum sex hormones and fertility in mice and rabbits are affected by Foeniculum vulgare. 45 They demonstrated that the use of 2% and 4% Foeniculum vulgare in the diet of male rabbits causes a significant increase in serum testosterone levels. One of the compounds of Foeniculum vulgare is isoflavones; this compound inhibits the activity of 5α-reductase and aromatase P450 enzymes.…”
Section: Discussionmentioning
confidence: 99%